Ijarah and lease ending with ownership and its implications for the bank's profits: A case study in the Emirates Islamic Bank and Emirates NBD (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The formula of Ijarah and Ijarah ending with ownership is one of the investment formulas in Islamic banks, so this research has shed light on it in order to benefit from the experiences of the research sample banks, This research aims to find a reliable way for Iraqi Islamic banks, namely (leasing and leasing ending with ownership) in order to invest their money without usurious interests, The problem of the research emerges through the lack of awareness of the Iraqi Islamic banks to work with different Islamic financing formulas and their inability to invest their money through the adoption of their administrations for different formulas, including the leasing, and this is reflected in the decrease and fluctuation of its profits, Therefore, the growth and importance of rental returns and rent-to-own ownership were measured and analyzed, as well as a study of the role and reflection of these returns on the profits of those Islamic banks for the period from (2012-2021) in addition to financial analysis through the use of profitability indicators, in addition to the comparison between Emirates Islamic Bank And Emirates NBD Bank, and the hypothesis that the research came up with is that Islamic banks achieve high returns through the use of the lease and lease-to-own-ownership formula, which are positively reflected on the profits of a bank.